RELIGIOUS EDUCATION FOR EARLY AGE - Silvi Amaliah; Muhammad Rizqi Romadhon (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
This research is done because it sees the confusion of parents to educate the religion ways for their child, but according to the Prophet Muhammad sallallaahu 'alaihi wasallam the child education must begin at an early age. Therefore the author intends to examine how the method of religious education for early childhood is appropriate. The research used is literature study research. This research method is used because the problem is related to the theoretical problems that exist in the literature related to the source of the study and discussion that can show the facts logically in order to produce a qualitative conclusion based on the analysis of induction, deduction and convergence. This study aims to determine the religious views of early childhood, the concept of religious education for early childhood, and the method of religious education for young children. The conclusion of this research is: Islam considers that children have the right to get proper education, parents are responsible for religious education of their children, the best method in educating children is the method of riyadlah or habituation.